Bifacial Color‐Tunable Transparent Photovoltaics for Application as Building‐Integrated Photovoltaics. Issue 8 (24th June 2021) - Kim, Sangho; Yi, Junsin; Kim, Joondong
Abstract : Transparent photovoltaics (TPVs) have attracted enormous attention due to their potential to be applied as building‐integrated photovoltaics (BIPV). Transparent and semitransparent photovoltaics have achieved a high level of efficiency, but there are still a number of issues that limit their application, such as their device size, lack of stability, and transmittance in the visible wavelength region. The excellent color implementation of a bifacial color‐tunable (BCT) TPV by tuning the indium tin oxide (ITO) thickness is demonstrated. The BCT TPV has a bifacial factor of 97.2% while maintaining an average visible transmittance (AVT) of 41.6%. The use of a 16 cm 2 large‐scale TPV device using a dry plasma fabrication process is also demonstrated. This dry process enables large‐scale device production and ensures long‐term device stability. The efficiency improvement with various background colors (blue 14%, red 25%, and white 35%) without any additional installation on the device is also confirmed. The BCT TPV is a promising candidate for BIPV applications due to its wide range of color tunability and excellent double‐sided photovoltaic operation, even under an indoor artificial light. Abstract : For the practical application of transparent building‐integrated photovoltaics, various colors are implemented by varying the thickness of the indium thin oxide film while maintaining the transparency and visibility of the device. Also, device power generation in both directions and performance improvement in various backgrounds are confirmed. This large‐area (16 cm 2 ), inorganic‐based transparent photovoltaic demonstrates stability for 150 days.